2020
DOI: 10.1075/mdm.5
|View full text |Cite
|
Sign up to set email alerts
|

The Multilingual Challenge for the Construction and Transmission of Scientific Knowledge

Abstract: Whereas it is now generally recognised that multilingualism is important for society, culture and the economy, the relevance of multilingualism for the world of science has still largely escaped attention. But science, too, is created and transmitted in and through communication. Today, the construction and transmission of knowledge is based on a growing monolingualism, with English as the lingua academica regarded as a condition of the universality of scientific knowledge. However, this idea is based on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 60 publications
0
1
0
1
Order By: Relevance
“…The other subcategory consists of studies focussing on more micro levels (e.g., at the mathematics classroom level, see Mesa and Chang, 2010 ; at the L2 classroom level, see Yu et al, 2019 ; at the knowledge construction level, 4 see Berthoud and Gajo, 2020 ; at the instructional task-design level, see Lambert and Zhang, 2019 ; Sert and Amri, 2021 ). For instance, Aubrey et al (2020) reported on a longitudinal study exploring the factors contributing to learners’ (lack of) engagement in an EFL classroom at one Japanese university; based on qualitative self-reported reflection data from 37 second-year sociology, they found that a lack of engagement could be attributed to causes, such as ‘lack of vocabulary’ and being unable to say what the student wanted to ‘say quickly in English’ (p. 8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The other subcategory consists of studies focussing on more micro levels (e.g., at the mathematics classroom level, see Mesa and Chang, 2010 ; at the L2 classroom level, see Yu et al, 2019 ; at the knowledge construction level, 4 see Berthoud and Gajo, 2020 ; at the instructional task-design level, see Lambert and Zhang, 2019 ; Sert and Amri, 2021 ). For instance, Aubrey et al (2020) reported on a longitudinal study exploring the factors contributing to learners’ (lack of) engagement in an EFL classroom at one Japanese university; based on qualitative self-reported reflection data from 37 second-year sociology, they found that a lack of engagement could be attributed to causes, such as ‘lack of vocabulary’ and being unable to say what the student wanted to ‘say quickly in English’ (p. 8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Souvent justifié par une recherche d'universalité des MOOC, elle-même motivée par des politiques institutionnelles et/ou de diffusion, le recours à une langue hégémonique n'est pas sans conséquence pour les processus de construction et de contextualisation des savoirs. Les travaux sur le plurilinguisme, notamment dans l'enseignement supérieur, ont montré que l'utilisation massive de l'anglais repose souvent sur une représentation des langues mettant en avant de manière parfois un peu simpliste sa fonction de communication et sous-exploitant leur potentiel pour la construction des connaissances (Berthoud et Gajo, 2020). Par ailleurs, l'homogénéisation non seulement des langues, mais également des formats discursifs et pédagogiques, induite par les grandes plateformes, tend vers des modèles universels de diffusion des connaissances (Altbach, 2014), gommant l'ancrage culturel des savoirs (Dillon, Wang et Tearle, 2007), pourtant présent tant du côté de la conception que de la réception (Fonseca et Gajo, 2020, 2021.…”
Section: Les Mooc Objets Linguistiques Et Langagiersunclassified